2009
DOI: 10.1158/0008-5472.can-09-1140
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Loss of Mucosa-Associated Lymphoid Tissue 1 Expression in Patients with Oral Carcinomas

Abstract: Mucosa-associated lymphoid tissue 1 (MALT1), which is located in a genomic region that encodes unknown tumor suppressor gene(s), activates nuclear factor-KB in lymphocyte lineages. However, its expression and role in the pathology of malignant tumors of epithelial origin is not known. In the present study, we examined MALT1 expression and its implications for the pathology of oral carcinomas. Immunostaining localized MALT1 in the nucleus of normal oral epithelial cells, but the expression was absent in 45.0% o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…Aggressive subsets of oral SCC cells frequently lose the keratinocyte-differentiation markers and express mesenchymal cell-specific molecules at the invasive front [28][32]. This indicates the presence and involvement of EMT in the carcinoma progression.…”
Section: Discussionmentioning
confidence: 99%
“…Aggressive subsets of oral SCC cells frequently lose the keratinocyte-differentiation markers and express mesenchymal cell-specific molecules at the invasive front [28][32]. This indicates the presence and involvement of EMT in the carcinoma progression.…”
Section: Discussionmentioning
confidence: 99%
“…HSC2 cells stably expressing FLAG-tagged full-length wild-type MALT1 ( wtMALT1 HSC2 cells) and the NH 2 terminal death and Ig-like domains-deleted dominant-negative MALT1 ( ΔMALT1 HSC2 cells; Che et al , 2004) and transfected vector alone ( mock HSC2 cells) were established previously (Chiba et al , 2009). They were maintained in 10% fetal bovine serum and 100 units per ml of penicillin/streptomycin-containing DMEM (Sigma-Aldrich, St. Louis, MO, USA) in a conventional 5% CO 2 incubator.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous study demonstrated that mucosa-associated lymphoid tissue 1 (MALT1) is expressed in the nucleus of oral epithelial cells (Chiba et al , 2009) and substitutes keratins depending on its expression (Kawamoto et al , 2013). The advanced carcinomas inactivate MALT1 expression by the promoter methylation, and the loss of expression worse the patient prognosis (Chiba et al , 2009). However, nothing is known about the role of loss of expression in the carcinoma progression at present.…”
mentioning
confidence: 99%
“…Since proteolytic degradation of the extracellular matrix releases growth factors (38), we should consider the impact of carcinoma cell-tissue interactions on the expression carefully. Furthermore, an intracellular signaling molecule, mucosa-associated lymphoid tissue 1, which suppresses the aggressive phenotype of oral carcinoma cells and is inactivated in the patients with worse prognosis directly affects FABP expression (39,40). Therefore both genetic and environmental factors provoke carcinoma cells to express FABP5.…”
Section: Discussionmentioning
confidence: 99%